The Effectiveness of Scrabble and Wordsearch Games to Teach Vocabulary to Students with Different Interests - Yulianti, Yulianti; Linggar Bharati, Dwi Anggani (Postgraduate Program, Universitas Negeri Semarang, 2017)
Many students feel difficult to memorize the vocabularies   given by the teacher. Students in my school like to act like learning while playing. In fact, the teacher almost never used media in   teaching and learning process.The objective of the study is to find out the effectiveness of scrabble and word search games on teaching vocabulary.The researcher applied quantitative and qualitative methods to collect the data. Quantitatively, the data were gathered through vocabulary test and questionnaire sheet. Vocabulary test was used to examine students? vocabulary achievement in the form of multiple choice and cloze test items. Questionnaire was given to the students in order to know the students? interest. Qualitatively, the observation checklist used to know level of vocabulary competence before using games.Then, I analysed the data from questionnaire and vocabulary test using t-test and ANOVA.The resultsshowed that Scrabble and wordsearch games were more effective to students. Mean score of  wordsearch strategy was higher than scrabble in vocabulary to high and low interest students. The last results indicated that there was no significant interaction among the teaching techniques (scrabble and word search games), interest, and students? vocabulary achievement.It can be concluded that taught by using scrabble or wordsearch was effective to high and low students. Mean score of the experimental and control class increased. There  were significant both of games .